2022
DOI: 10.1088/1748-9326/ac49ba
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of 319 wind farms on surface temperature and vegetation in the United States

Abstract: The development of wind energy is essential for decarbonizing energy supplies. However, the construction of wind farms changes land surface temperature (LST) and vegetation by modifying land surface properties and disturbing land-atmosphere interactions. In this study, we used MODIS satellite data to quantify the impacts of 319 wind farms on local climate and vegetation in the United States. Our results indicated insignificant impacts on LST during the daytime but significant warming of 0.10°C on annual mean n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…In another study, the inhibition of the summer gross primary production by onshore wind farms in Hebei after their completion was 8.9%, and the annual net primary production suppression was 4% (Tang et al, 2017). Although onshore wind farms inhibit vegetation growth, studies have found that the effect of onshore wind farm impacts was mainly concentrated inside the wind farms, and the most degraded areas were inside the wind farms, which was verified by diagnostic model tests (Qin et al, 2022;Aksoy et al, 2023).…”
Section: Growth Of Plant Communitiesmentioning
confidence: 85%
See 2 more Smart Citations
“…In another study, the inhibition of the summer gross primary production by onshore wind farms in Hebei after their completion was 8.9%, and the annual net primary production suppression was 4% (Tang et al, 2017). Although onshore wind farms inhibit vegetation growth, studies have found that the effect of onshore wind farm impacts was mainly concentrated inside the wind farms, and the most degraded areas were inside the wind farms, which was verified by diagnostic model tests (Qin et al, 2022;Aksoy et al, 2023).…”
Section: Growth Of Plant Communitiesmentioning
confidence: 85%
“…Although in situ data monitoring has the advantages of high data accuracy and distinctive features, it is limited in scale and has a major disadvantage, especially in assessing the ecological and climatic impacts of onshore wind farms in a large-scale context. In situ data monitoring can provide reliable information for the inversion of remotely sensed data, such as inversely assessing near-surface temperatures at different times (Walsh-Thomas et al, 2012; Zhou et al, 2012; Zhou et al, 2013; Harris et al, 2014; Slawsky et al, 2015; Chang et al, 2016; Liu et al, 2021b; Luo et al, 2021; Liu et al, 2022a; Ma et al, 2022; Qin et al, 2022), vegetation indexes (Li et al, 2016; Tang et al, 2017; Xia and Zhou, 2017; Wu et al, 2019; Liu et al, 2022b; Aksoy et al, 2023), landscape patterns (Zhang et al, 2016; Diffendorfer et al, 2019; Guo et al, 2020) and other indicators in order to assess the impacts of onshore wind farms on the localized eco-climate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wake effect of wind turbines generates turbulence that spreads for kilometers downwind, the buffer should be outside the wake range. Meanwhile, the buffer should not be too far from the WF to share a similar climate background (Zhou et al 2012, Tang et al 2017, Qin et al 2022. The desert pixels are finally filtered by MCD12Q1 IGBP land cover data (figure S2), the filtered pixels are defined as wind farm pixels (WFPs) and buffer pixels (BUPs) in the following text.…”
Section: Study Areamentioning
confidence: 99%
“…However, when the ABL is unstable, with warmer air near the surface and cooler air in the upper layer, the WF impact on daytime LST is more complicated. Rotations of the wind turbine blades mix the cooler upper air and the warmer near-surface air and cool down the land surface (Miller and Keith 2018, Zhou et al 2020, Qin et al 2022, solar radiation heats the surface and creates upward convection. Besides, when the ABL is neutral, the temperatures of upper and lower air layers are approximate and the heat convection is near zero.…”
Section: Introductionmentioning
confidence: 99%